2018
DOI: 10.1002/term.2759
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐132 directs human periodontal ligament‐derived neural crest stem cell neural differentiation

Abstract: Neurogenesis is the basis of stem cell tissue engineering and regenerative medicine for central nervous system (CNS) disorders. We have established differentiation protocols to direct human periodontal ligament-derived stem cells (PDLSCs) into neuronal lineage, and we recently isolated the neural crest subpopulation from PDLSCs, which are pluripotent in nature. Here, we report the neural differentiation potential of these periodontal ligament-derived neural crest stem cells (NCSCs) as well as its microRNA (miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…It is important to mention that the hPDLSCs-derived neural-like cells located in the NSC niches show neural stem morphology, which suggests hPDLSCs-derived neural-like cells may achieve a correct polarization in vivo. www.nature.com/scientificreports www.nature.com/scientificreports/ Therefore, our results provide additional evidence that it is possible to differentiate hPDLSCs to neuron-like cells, as suggested by their neural-crest origin, stem cell characteristics and neural differentiation potential both in vitro and in vivo [13][14][15][16][17][18][19][20][21][22][23][24] . However, it is important to mention that future research is required to resolve the potential limitations in their medical application 10,14,46 , and also to optimize the diversity of in vitro neural induction protocols that have been designed for dental stem cells 22 .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…It is important to mention that the hPDLSCs-derived neural-like cells located in the NSC niches show neural stem morphology, which suggests hPDLSCs-derived neural-like cells may achieve a correct polarization in vivo. www.nature.com/scientificreports www.nature.com/scientificreports/ Therefore, our results provide additional evidence that it is possible to differentiate hPDLSCs to neuron-like cells, as suggested by their neural-crest origin, stem cell characteristics and neural differentiation potential both in vitro and in vivo [13][14][15][16][17][18][19][20][21][22][23][24] . However, it is important to mention that future research is required to resolve the potential limitations in their medical application 10,14,46 , and also to optimize the diversity of in vitro neural induction protocols that have been designed for dental stem cells 22 .…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, hPDLSCs expressed ion channel receptors 19 and displayed inward currents conducted through voltage-gated sodium (Na+) channels and spontaneous electrical activities after neurogenic differentiation 20,21 . Therefore, the neural crest origin 14,15 and neural differentiation potential both in vitro and in vivo [13][14][15][16][17][18][19][20][21][22][23][24] , make human periodontal ligament stem cells (hPDLSCs) interesting for investigating stem cell to neuron differentiation mechanisms.…”
mentioning
confidence: 99%
“…Since then, multiple studies have shown that miRNAs play significant roles in cartilage homeostasis. Moreover, there is evidence that miRNAs are important players in maintaining the health of all joint tissues, including muscle [ 43 47 ], cartilage [ 48 , 49 ] and ligament and tendon [ 50 , 51 ]. Whilst there is very little known about the role of specific microRNAs in muscle wasting during OA, with only one microRNA, miR-141, suggested to have a function in the ageing of the multiple tissues of the musculoskeletal system [ 52 ], multiple studies have shown the involvement of miRNAs in muscle wasting [ 53 55 ].…”
Section: Micrornas As Novel Therapeutic Targets For Muscle Wasting Dumentioning
confidence: 99%
“…The importance of microRNAs in the function of musculoskeletal tissues was also demonstrated in depletion studies of Dicer, a key enzyme in miRNA biogenesis. The deletion of Dicer in chondrocytes resulted in defective cell proliferation and differentiation [ 51 ], and the deletion of Dicer in bone progenitors was associated with defective bone formation [ 56 ]. A satellite cell–specific Dicer knockout resulted in mild muscle fibre atrophy over time [ 57 ], and microRNAs maintain muscle homeostasis through the control of muscle hypertrophy and atrophy and muscle adaptation to exercise [ 58 60 ].…”
Section: Micrornas As Novel Therapeutic Targets For Muscle Wasting Dumentioning
confidence: 99%
“…Report also revealed that neural crest subpopulation which can directly differentiate into neural lineage could be isolated from dental tissue. 102 These cells migrate to the lesion place in order to replace the necrotic tissue. 43,44,48 101 Neurotrophic factors secreted by DSCs promote the regeneration of axons.…”
Section: Mechanis Ms Underlying Dsc S-med Iated Neur Al Repairmentioning
confidence: 99%